TV Presenter Skills An Assessment of Speech and Body Language Skills for Kurd Tv Presenters, from the Point of View of the Media Specialist (Raparin Journal of Humanities (RJH), 2021)
Although for many years the new media has occupied large areas of the world of media and communication, television has not lost its importance and the importance of its programs, while channels are constantly trying to renew and develop their technologies and contents. Hence the most difficult and fateful task on the radio and tv presenter. This research is a theoretical and applied attempt to analyze and discover the skills of the tv presenter in both the fields of speech and body language.